2016
DOI: 10.5115/acb.2016.49.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage density in pharyngeal and laryngeal muscles greatly exceeds that in other striated muscles: an immunohistochemical study using elderly human cadavers

Abstract: Macrophages play an important role in aging-related muscle atrophy (i.e., sarcopenia). We examined macrophage density in six striated muscles (cricopharyngeus muscle, posterior cricoarytenoideus muscle, genioglossus muscle, masseter muscle, infraspinatus muscle, and external anal sphincter). We examined 14 donated male cadavers and utilized CD68 immunohistochemistry to clarify macrophage density in muscles. The numbers of macrophages per striated muscle fiber in the larynx and pharynx (0.34 and 0.31) were 5–6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In addition to results obtained from mice, we confirmed an increased HGF , PDGFRa , and PLAT transcript levels and CD90 + FAPs in human CP muscles. The increased HGF levels in CP is consistent with a previous report examining several craniofacial muscles, including CP muscles from 14 cadavers ( Rhee et al, 2016 ). These data indicate the translational potential of our data generated in mice.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to results obtained from mice, we confirmed an increased HGF , PDGFRa , and PLAT transcript levels and CD90 + FAPs in human CP muscles. The increased HGF levels in CP is consistent with a previous report examining several craniofacial muscles, including CP muscles from 14 cadavers ( Rhee et al, 2016 ). These data indicate the translational potential of our data generated in mice.…”
Section: Discussionsupporting
confidence: 92%
“…A study of older human cadavers showed that the macrophage density in the pharyngeal and laryngeal muscles was five‐ to sixfold greater than that for the striated muscles of the tongue, shoulder and anus. Whereas the potential thinning and death of striated muscle fibers have been speculated to occur at greater rates in the pharyngeal and laryngeal muscles, macrophage migration is suspected to have possible protective effects on aging in these muscles through the actions of macrophage‐related cytokines …”
Section: Specificity Of the Swallowing Musclesmentioning
confidence: 99%
“…Whereas the potential thinning and death of striated muscle fibers have been speculated to occur at greater rates in the pharyngeal and laryngeal muscles, macrophage migration is suspected to have possible protective effects on aging in these muscles through the actions of macrophagerelated cytokines. 29 When dealing with sarcopenia of the swallowing-related muscles, careful and cautious discussion is critical; the embryological origin of the muscles and the characteristics of the special visceral muscles should be taken into consideration.…”
Section: Specificity Of the Swallowing Musclesmentioning
confidence: 99%
“…Glottal closure in the elderly can be mostly incomplete due to atrophic changes of the TA muscle with aging, especially in men . Atrophy of the vocal cords in the elderly results from the scarcity of elastic fibers and hyaluronic acid, and combined with atrophy of the vocal cord muscles could affect phonation . A cross‐innervation pattern to the TA muscle via the external branch of the superior laryngeal nerve and the classical recurrent laryngeal nerve further increases the challenge of understanding and treating dysfunction of the TA muscle .…”
Section: Discussionmentioning
confidence: 99%